Kajian sifat kimia brownies panggang dengan substitusi mocaf dan tepung kelor - Dwiani, Afe; Yuniartini, Ni Luh Putu Sherly (Universitas Muhammadiyah Mataram, 2022)
Brownies are wheat-based snack products that prefer by peoples. The need for wheat increased every year. One of the local flours that can reduce people's dependence on the use of wheat is mocaf /modified cassava flour. Brownies have a high carbohydrate and fat content but a low vitamin and mineral content. Therefore, the addition of moringa leaf flour is need. The purpose of this study was to determine the effect of substitution of mocaf and moringa leaf flour on the chemical quality of brownies. The treatment of this study is the combination of flour, mocaf and moringa leave flour become six treatment, namely A0 = 50% flour : 50% mocaf : 0 moringa leaf flour (control), A1 = 47,5% flour : 47,5% mocaf : 5% moringa leaf flour, A2 = 45% flour : 45% mocaf : 10% moringa leaf flour, A3 = 42,5% flour : 42,5% mocaf : 15 % moringa leaf flour, A4 = 40% flour : 40% mocaf : 20% moringa leaf flour and A5 = 37,5% flour : 37,5% mocaf : 25% moringa leaf flour. The study results show that the addition of moringa leaf flour significantly influences the chemical properties (moisture, ash and protein content) on brownies. According to standard (SNI), the best treatment for water content is A0 treatment (wheat flour 50%: mocaf 50%: moringa leaf flour 0%) with a value of 25.21%, for ash and protein content are produced by A5 treatment (wheat flour 37.5%: mocaf 37.5%: moringa leaf flour 25%) with the value respectively are 2.80% and 6.68%.